Inequalities in access to total hip arthroplasty for hip fracture: population-based study - Perry, D; Metcalfe, D; Griffin, X; Costa, M (BMJ Publishing Group, 2016)
Objectives: To determine whether the use of total hip arthroplasty (THA) amongst individuals with a displaced intracapsular fracture of the femoral neck is based on national guidelines, or if there are systematic inequalities. Design: Observational cohort study using the National Hip Fracture Database (NHFD). Setting: All hospitals that treat adults with hip fractures in England, Wales, and Northern Ireland. Participants: Patients within the NHFD (all aged >60 years old), who received operative treatment for a non-pathological displaced intracapsular hip fracture between 1st July 2011 and 31st April 2015. Main outcome measures: Provision of THA to patients considered eligible under criteria published by the National Institute for Health and Care Excellence (NICE). Results: 114,119 hip fracture patients were included, 11,683 (10.2%) of which underwent THA. 32.0% that appeared to satisfy the NICE criteria received a THA, and 42.0% of patients that underwent THA did not satisfy the criteria. A recursive-partitioning algorithm found that the NICE eligibility criteria did not optimally explain which patients underwent THA. A model with superior explanatory power drew distinctions that are not supported by NICE: age >77 years and use of a stick for ambulation. Amongst patients satisfying the NICE eligibility the use of THA was limited based on higher age (OR 0.88, 95% CI 0.87 to 0.88), lower Abbreviated Mental Test Score (OR 1.44, 95% CI 1.34 to 1.54), higher American Society of Anesthesiologists (ASA) score (OR 0.74, 95% CI 0.66 to 0.84), male sex (OR 0.85, 95% CI 0.77 to 0.93), walking with a stick (0.32, 95% CI 0.28 to 0.35), and quintiles of increasing socioeconomic area deprivation (1.0 (ref) lowest quintile vs. highest quintile 1.30, 95% CI 1.13 to 1.51). Patients receiving treatment during the working week were more likely to receive THA than those at the weekend (OR 1.12, 95% CI 1.04 to 1.21). Conclusions: There are wide disparities in the use of THA amongst individuals with hip fractures and compliance with NICE guidance is poor. Patients with higher levels of socioeconomic deprivation and requiring surgery at the weekend were less likely to receive THA. Inconsistent compliance with NICE recommendations means that the optimal treatment for older adults with hip fractures can depend on where and when they present to hospital.